PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP PEMAHAMAN SISWA PADA MATERI PERUBAHAN WUJUD BENDA KELAS 4 SD - Aisah, Siti; Kusuma, Rendra Sakbana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine whether there is an influence on the level of student understanding by using the Talking Stick Learning Model in science subjects on the material of Changes in the Form of Objects class 4 at UPTD SDN Sepulu 01 with this quantitative research using the research design used is a pre- Experinmental Designs design. The sample used by 4th grade students as many as 22 students in total. The instrument used is a test of student understanding of learning. While the analysis test is validity test, reliability, normality and paired sample t-test with the help of IBM SPSS v21.0 application. This is evidenced by using the talking stick model on the level of student understanding obtained a significant value (2-tailed) of 0.000 <0.05 which states that there is a difference in the level of student understanding by using the talking stick model.